The malignant signature gene of cancer-associated fibroblasts serves as a potential prognostic biomarker for colon adenocarcinoma patients - Zhang, Hao; Zhuang, Zirui; Hong, Li; Wang, Ruipeng; Xu, Jinjing; Tang, Youyuan (Frontiers in Immunology, 2025)
BackgroundColon adenocarcinoma (COAD) is the most frequently occurring type of colon cancer. Cancer-associated fibroblasts (CAFs) are pivotal in facilitating tumor growth and metastasis; however, their specific role in COAD is not yet fully understood. This research utilizes single-cell RNA sequencing (scRNA-seq) to identify and validate gene markers linked to the malignancy of CAFs.MethodsScRNA-seq data was downloaded from a database and subjected to quality control, dimensionality reduction, clustering, cell annotation, cell communication analysis, and enrichment analysis, specifically focusing on fibroblasts in tumor tissues compared to normal tissues. Fibroblast subsets were isolated, dimensionally reduced, and clustered, then combined with copy number variation (CNV) inference and pseudotime trajectory analysis to identify genes related to malignancy. A Cox regression model was constructed based on these genes, incorporating LASSO analysis, nomogram construction, and validation.Subsequently, we established two FNDC5-knockdown cell lines and utilized colony formation and transwell assays to investigate the impact of FNDC5 on cellular biological behaviors.ResultsUsing scRNA-seq data, we analyzed 8,911 cells from normal and tumor samples, identifying six distinct cell types. Cell communication analysis highlighted interactions between these cell types mediated by ligands and receptors. CNV analysis classified CAFs into three groups based on malignancy levels. Pseudo-time analysis identified 622 pseudotime-related genes and generated a forest plot using univariate Cox regression. Lasso regression identified the independent prognostic gene FNDC5, which was visualized in a nomogram. Kaplan-Meier survival analysis confirmed the prognostic value of FNDC5, showing associations with T stage and distant metastasis. In vitro experiment results demonstrated a strong association between FNDC5 expression levels and the proliferative, migratory, and invasive abilities of colon cancer cells.ConclusionWe developed a risk model for genes related to the malignancy of CAFs and identified FNDC5 as a potential therapeutic target for COAD.